Domestic Investment in Pakistan: An Analysis Across Different Political Regimes - Shabbir, Muhammad; Shaheen, Imrab; Qayyum, Fahrat (International Journal of Economics and Financial Issues, 2020)
This study has been conducted to find out the impact of political and economic variables on domestic investment of Pakistan. For this purpose secondary data for thirty five years has been collected according to the variables of this study. To analyze the data ARDL bound test procedure has been applied to assess long run relationshipand ARDL based ECM applied to check short run associationof political and economic variables on domestic investment whereasAugmented Dickey Fuller test is applied to check stationary of data. Our findings declared that gross domestic product, foreign direct investment, foreign debt and domestic credit to private sector positively affect domestic investment in Pakistan whereas interest rate, foreign aid, inflation and non-democratic government have negative relation with domestic investment in long run. Dictatorial dummy and credit to private sector has insignificant influence in long run whereas in short run, non democratic dummy influences domestic investment significantly. Results are accordant with classical and Keynesian views.Overall it is concluded that domestic investment decisions have no concern to regime type but political and economic stability and law and order conditions are necessary to promote domestic investment. Keywords: Political regime, Gross domestic product, foreign debt, Domestic investment, Interest rate. JEL Classifications: O1, O2, O4, A3, E62 DOI: https://doi.org/10.32479/ijefi.10444